Degradation of the Met tyrosine kinase receptor by the ubiquitin-proteasome pathway. - Jeffers, M (1997)
The Met tyrosine kinase receptor is a widely expressed molecule which mediates pleiotropic cellular responses following activation by its ligand, hepatocyte growth factor/scatter factor (HGF/SF). In this communication we demonstrate that significant Met degradation is induced by HGF/SF and that this degradation can be blocked by lactacystin, an inhibitor of proteasome activity. We also show that Met is rapidly polyubiquitinated in response to ligand and that polyubiquitinated Met molecules, which are normally unstable, are stabilized by lactacystin. Both HGF/SF-induced degradation and polyubiquitination of Met were shown to be dependent on the receptor possessing intact tyrosine kinase activity. Finally, we found that a normally highly labile 55-kDa fragment of the Met receptor is stabilized by lactacystin and demonstrate that it represents a cell-associated remnant that is generated following the ligand-independent proteolytic cleavage of the Met receptor in its extracellular domain. This truncated Met molecule encompasses the kinase domain of the receptor and is itself tyrosine phosphorylated. We conclude that the ubiquitin-proteasome pathway plays a significant role in the degradation of the Met tyrosine kinase receptor as directed by ligand-dependent and -independent signals. We propose that this proteolytic pathway may be important for averting cellular transformation by desensitizing Met signaling following ligand stimulation and by eliminating potentially oncogenic fragments generated via extracellular cleavage of the Met receptor.